Experimental investigation on torsional strengthening of box RC structures using NSM FRP - Gowda, Chandan Chinnagiri (2018)
The near surface mounted (NSM) technique is a strengthening method that provides additional reinforcement by means of strips or bars embedded into grooves made in the concrete cover of reinforced concrete (RC) elements. The effectiveness of using NSM fibre reinforced polymer (FRP) bars or strips to enhance the shear and flexural capacity of RC elements has been demonstrated over the past decade. However, the idea of using NSM FRP reinforcement to address issues related to deficient torsional performance is yet to be explored. Torsional strengthening of RC elements (e.g. bridge girders, transfer beams) may be necessary due to degradation of materials, changes in the design codes, deficiencies in the initial design, changes in building usage etc. This paper investigates the torsional strengthening of thin walled tubular RC beams using NSM CFRP laminates. The experimental program involved testing of six box sectioned RC beams, including two reference beams (with and without shear reinforcement) and four beams strengthened with different arrangements of NSM CFRP reinforcement, providing varying longitudinal and transverse reinforcement ratios. All the strengthening proposals resulted in significant increase in torsional moment capacity, ductility, stiffness in the elasto-plastic range and were very efficient in arresting crack propagation, proving the effectiveness of NSM strengthening technique for torsional strengthening. The proposed experimental program is described in detail and the main results are presented and discussed.